Introduction to Creativity and Innovation for Engineers, Global Edition - Walesh, Stuart G.; Walesh, Stuart (Pearson International Content, 2018)
For courses in creativity and innovation for engineers.   Emphasising the Importance of Innovation and Creativity for Engineers This first edition of Introduction to Creativity and Innovation for Engineers was primarily designed for engineering students interested in acquiring knowledge, skills, and attitudes (KSA) that will help them be more creative and innovative. While intended primarily for engineering students, the widely applicable principles, ideas, tools, and methods introduced will also be useful for practicing engineers and as well as members of other disciplines.   The text argues for a “whole-brain” approach to the study of engineering, using neuroscience as a foundation. While the left brain (logical and analytic) is essential to the study of engineering, the author believes that engineering students and practitioners will be more successful if they learn to also engage in more right brain processing (intuitive and emotional). Similarly, they should draw on knowledge of conscious and subconscious thinking and view the brain as a muscle that can be continuously strengthened.   Building on that “Neuroscience 101” foundation, the text prepares future and current engineers to work smarter–either as individuals or within teams and organisations–by generating and developing new ideas. The nine chapter structure uses clear objectives, many examples, and numerous exercises to explicate its methods, ultimately enabling students and practitioners to realise that they’re already capable of creative - innovative thinking. They only need to apply the 20 methods described in the book to unlock their brain’s natural capabilities and then produce creative-innovative results for their benefit and for the benefit of others. The full text downloaded to your computer With eBooks you can: search for key concepts, words and phrases make highlights and notes as you study share your notes with friends eBooks are downloaded to your computer and accessible either offline through the Bookshelf (available as a free download), available online and also via the iPad and Android apps. Upon purchase, you'll gain instant access to this eBook. Time limit The eBooks products do not have an expiry date. You will continue to access your digital ebook products whilst you have your Bookshelf installed.